Structural, electrical and optical properties of ion-conducting Na6PS5Cl, Na6PS5Br, and Na7PS6 compounds. (December 2021) - Studenyak, I.P.; Pogodin, A.I.; Studenyak, V.I.; Kokhan, O.P.; Azhniuk, Yu.M.; Solonenko, D.; Daróczi, L.; Kökényesi, S.; Zahn, D.R.T.
Abstract: Sodium halogenthiophosphates Na6 PS5 Br and Na6 PS5 Cl as well as halogen-free Na7 PS6 were synthesized by a two-step technique from elemental substances and relevant sodium halides. The elemental composition of the samples obtained was determined by energy-dispersive X-ray spectroscopy. The crystalline structure of the synthesized Na6 PS5 Br and Na6 PS5 Cl compounds is confirmed by X-ray diffraction and Raman spectroscopy. The Raman spectra of Na6 PS5 Br and Na6 PS5 Cl reveal a noticeable similarity to those of chemically related copper, potassium, and lithium halogenthiophosphates as well as the synthesized Na7 PS6 compound. The electrical conductivity of Na6 PS5 Br, Na6 PS5 Cl, and Na7 PS6 is shown to be predominantly ionic. Graphical abstract: Image 1 Highlights: The crystalline structure of Na6 PS5 Br and Na6 PS5 Cl compounds is revealed. XRD and Raman spectra of Na6 PS5 Br, Na6 PS5 Cl, and Na7 PS6 are studied. Electrical conductivity of Na6 PS5 Br, Na6 PS5 Cl, and Na7 PS6 is measured.